Constraining local ocean dynamic sea-level projections using observations - D. Le Bars; I. Keizer; S. Drijfhout; S. Drijfhout (Ocean Science)
The redistribution of ocean water volume under ocean–atmosphere dynamical processes results in sea-level changes. This process, called ocean dynamic sea level (ODSL) change, is expected to be one of the main contributors to sea-level rise along the western European coast in the coming decades. State-of-the-art climate model ensembles are used to make 21st century projections of this process, but there is a large model spread. Here, we use the Netherlands as a case study and show that the ODSL rate of change for the period 1993–2021 correlates significantly with the ODSL anomaly at the end of the century and can therefore be used to constrain projections. Given the difficulty of estimating ODSL changes from observations on the continental shelf, we use three different methods providing seven observational estimates. Despite the broad range of observational estimates, we find that 4 to 16 CMIP6 models have rates above the observational range and 0 to 1 below. We compare four model selection methods which differ in the way the uncertainty in the rate estimation is considered. We find that for stricter selection methods the rate of ODSL is closer to the observational range, and the uncertainty in future change is reduced. The influence of model selection is largest for the low emission scenario SSP1-2.6. We discuss the advantages and disadvantages of those selection methods and their suitability for different users.